Prevalence and Antimicrobial Susceptibility Pattern of Klebsiella Pneumoniae Isolated from Various Clinical Specimens in a Tertiary Care Hospital in Bangladesh - Sonia, Suraiya Jahan; Afroz, Shadia; Md Rasheduzzaman, -; Uddin, Kazi Hafiz; Shamsuzzaman, SM (Medicine Today, 2020)
Introduction:Klebsiella pneumoniae are common causative agents of various infections and are of great concern for developing resistance against commonly prescribed antibiotics. This study gives an account of isolation of K. pneumoniae from various clinical specimens and their antimicrobial susceptibility, in a tertiary care hospital of Bangladesh. Materials and Methods: Various clinical specimens like urine, wound swab, sputum, blood and endotracheal aspirates were collected and processed for isolation of K. pneumoniae followed by their antimicrobial susceptibility testing. Results: Among the 316 samples that yielded culture positivity, K. pneumoniae were identified as second most common organism. The highest yield of K. pneumoniae (37.33%) were observed from wound swab followed by sputum (26.67%). Most of the isolates were resistant to sulphamethoxazole-trimethoprim (90.67%) and ceftriaxone (90.67%) followed by cefotaxime (89.33%), ceftazidime (89.33%) and cefuroxime (89.33%). The most sensitive antibiotic for the isolates was tigecycline. Conclusion: Isolated K. pneumoniae showed resistance to commonly prescribed antibiotics, which is very alarming and showing the importance on continuous monitoring and strict antimicrobial policy. Medicine Today 2020 Vol.32(2): 95-99